Enhanced thermoelectric performance of hot-press Bi-doped n-type polycrystalline PbS. (January 2021) - Li, Yihuai; Wu, Zihua; Lin, Jinhao; Wang, Yuanyuan; Mao, Jianhui; Xie, Huaqing; Li, Zhen
Abstract: Lead sulfide (PbS) is a type of promising thermoelectric materials which is consist of elements with high natural abundance. However, the relatively low conversion efficiency limits its further application due to the high lattice thermal conductivity of PbS compared with that of PbTe. It has been widely accepted that nanostructuring and doping are effective ways to enhance the thermoelectric properties. Herein, nano/micro structure Bi doped PbS materials have beensynthesized by a facile method of hydrothermal synthesis. The nano/micro structure material systems exist abundant interface which could scatter mid- and low-frequency phonons effectively, combined with point defect such as Bi–Pb scattering high-frequency phonons, and thus the results show that the lattice thermal conductivity of PbS decreases with the increasing concentration of Bi 3+ doping as expected. Moreover, the optimal power factor (PF) can be obtained by tuning the carrier concentration and mobility at the same time. The optimal thermoelectric figure of merit (ZT) can reach 0.89 for Pb0.96 Bi0.04 S at 773K and rises with the increase of the temperature without sign of saturation. Our work may shed light to further possible and environmentally friendly application of PbS-based thermoelectric materials.